(untitled) (Prosiding Keislaman dan Sains, 2025)
This research aims to develop morality, morals and personality development for all students and make it a medium in the application in everyday life. The development of personality is to facilitate students in learning about the procedures for filial piety to parents and achieving the pleasure of Allah SWT. This research is a type of development research by referring to the postulates of Islamic law with the aim of making humans who are morally good based on the interpretations of scholars confident and responsible. Namely, what is written in several famous interpretations of tafsir among them tafsir jalalain, tafsir qurtubi, tafsir misbah. Personal guidance material, learning media experts and supervising teachers, 2nd semester students of Islamic sharia economic law STAI Ibnu Sina Batam and also guided by teachers inside and outside the school, who are experts in the field of religious science based on events that occur in the field or in the middle of society. Thus students can improve the quality of their filial piety to both parents and ultimately get a position on the side of Allah as a pious child who is devoted to both parents and gets the pleasure of Allah SWT. Thus there will be no children who have no manners and manners towards parents or disobedience.